The effect of watching the satellite programs on the skills of the talented students at the Eastern Region (Dammam) in the Kingdom of Saudi Arabia - Alomari, Abdullah Salem Ahmad (Journal of Educational and Psychological Sciences, 2020)
The present study aimed to reveal the relationship between the quality of space programs watched by children and the social skills of these children،  the study is also trying to identify the relationship between the number of hours watching this space programs and the social skills for these children. The study used a descriptive approach،  the study sample consisted of 215 boys and girls aged between 9- 12 years schools of Al- Dammam in Saudi Arabia،  the researcher used to identify children's programs television watched by children،  where the researcher in this study on the method of analysis of variance One-way Analysis of Variance and Scheffe test for multiple comparisons Multiple Comparison،  which resulted in findings on the lack of social skills for different dimensions: emotional sensitivity،  emotional and adjustment،  and the overall degree of social skills depending on the type of space programs that children watch. In addition to the lack of different social skills for the dimensions: emotional expression،  sensitivity،  emotionality،  and social expression،  and social sensitivity،  and the overall degree of social skills،  while the different settings of emotional and social adjustment depending on the number of hours watching TV channels،  for children who watch satellite channels less.
Keywords: satellite programs; social skills; talent students